ANALITYCAL HIRARCHY PROCESS (AHP) DALAM KEBIJAKAN PROGRAM PENANGGULANGAN KEMISKINAN PADA PEMERINTAH KOTA MEDAN - Irfan, Irfan; Deli, Leni (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
This study aims to determine the priority scale in determining poverty reduction policies in Medan City. Where the hierarchy obtained from the data analysis will determine which sectors are prioritized to be developed first, from the four defined sectors, namely the economic, social and education sectors. The quantitative approach is the basis of this research, so that data can be used using interviews conducted with the Mayor / Deputy Mayor of Medan, the SKPD of Medan City (Executive), Members of the Medan City DPRD (Legislative), and Community Leaders. A literature study was conducted in the form of information-documents in soft and hard copy form. The analysis in this research uses Analytical Hierarchy Process (AHP). The findings of the study state that the establishment of poverty reduction policies in Medan City based on hierarchy are first, the economic sector in Micro, Small and Medium Enterprises by providing business capital. Second, the education sector from the collection of educational facilities and infrastructure with teaching and learning programs. Third, the social sector by providing educational assistance in the form of school equipment assistance, working capital assistance in the form of providing business facilities, and health assistance in the form of obtaining health services. Fourth, the health sector with the establishment of Type A hospitals, the establishment of medical centers by establishing puskesmas.